`f(x)=e^(-2x)` Prove that the Maclaurin series for the function converges to the function for all x

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Maclaurin series is a special case of Taylor series that is centered at `c=0` . The expansion of the function about 0 follows the formula:

`f(x)=sum_(n=0)^oo (f^n(0))/(n!) x^n`


`f(x)= f(0)+(f'(0))/(1!)x+(f^2(0))/(2!)x^2+(f^3(0))/(3!)x^3+(f^4(0))/(4!)x^4 +...`

To determine the Maclaurin polynomial of degree n=5 for the given function `f(x)=e^(-2x)` , we may apply the formula for Maclaurin series..

To list derivative functions `f^n(x)` , we may apply derivative formula for exponential function: `d/(dx) e^u = e^u * (du)/(dx)` .


Let `u =-2x` then `(du)/(dx)= -2 .`

`d/(dx) e^(-2x) = e^(-2x) *(-2)`

                 `= -2e^(-2x)`

Applying `d/(dx) e^(-2x)= -2e^(-2x)`   for each derivative function, we get:

`f'(x) = d/(dx) e^(-2x)`


`f^2(x) = d/(dx) (- 2e^(-2x))`

            `=-2 d/(dx) (e^(-2x)) `



`f^3(x) = d/(dx) (4e^(-2x))`

            `=4d/(dx) (e^(-2x)) `



 `f^4(x) = d/(dx) (- 8e^(-2x))`

             ` =-8 d/(dx) (e^(-2x)) `



 Plug-in `x=0` for each `f^n(x)` , we get:

 `f(0) =e^(-2*0) =1`

 `f'(0) =-2e^(-2*0)=-2`

 `f^2(0) =4e^(-2*0)=4`

 `f^3(0) =-8e^(-2*0)=-8`

 `f^4(0) =16e^(-2*0)=16`

Note: `e^(-2*0) = e^0 = 1.`

 Plug-in the values on the formula for Maclaurin series, we get:

 `sum_(n=0)^oo (f^n(0))/(n!) x^n`

 `= 1+(-2)/(1!)x+4/(2!)x^2+(-8)/(3!)x^3+16/(4!)x^4+...`

 `= 1-2/(1!)x+4/(2!)x^2-8/(3!)x^3+16/(4!)x^4+...`

 ` =sum_(n=0)^oo (-2)^n/(n!)x^n`

 `=sum_(n=0)^oo (-2x)^n/(n!)`

To determine the interval of convergence for the Maclaurin series:` sum_(n=0)^oo (-2x)^n/(n!)` , we may apply Ratio Test.  

In Ratio test, we determine the limit as: `lim_(n-gtoo)|a_(n+1)/a_n| = L.`

The series converges absolutely when it satisfies `Llt1` .

For the  Maclaurin series: `sum_(n=0)^oo (-2x)^n/(n!)` , we have:



`1/a_n= (n!)/(-2x)^n`


            ` =((-2x)^n*(-2x)^1)/((n+1)*(n!))`

             ` =((-2x)^n(-2x))/((n+1)*(n!))`

Applying the Ratio test, we set-up the limit as:


                         ` =lim_(n-gtoo)|((-2x)^n(-2x))/((n+1)*(n!))*(n!)/(-2x)^n|`

Cancel out common factors: `(-2x)^n`  and `(n!)` .


Evaluate the limit.

`lim_(n-gtoo)|(-2x)/(n+1)|=|-2x| lim_(n-gtoo)|1/(n+1)|`

                       ` =|2x|lim_(n-gtoo)1/(n+1)`

                       ` =|2x|* 1/oo`

                        `= |2x|*0`

                        ` =0`

The `L=0` satisfies ` Llt1` for all `x` .

Thus, the Maclaurin series: `sum_(n=0)^oo (-2x)^n/(n!)` is absolutely converges for all `x` .

Interval of convergence: `-ooltxltoo`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial